A Class of FeIII Macrocyclic Complexes with Alcohol Donor Groups as Effective T1 MRI Contrast Agents. (20th December 2019) - Snyder, Eric M.; Asik, Didar; Abozeid, Samira M.; Burgio, Ariel; Bateman, Gage; Turowski, Steven G.; Spernyak, Joseph A.; Morrow, Janet R.
Abstract: Early studies suggested that Fe III complexes cannot compete with Gd III complexes as T1 MRI contrast agents. Now it is shown that one member of a class of high‐spin macrocyclic Fe III complexes produces more intense contrast in mice kidneys and liver at 30 minutes post‐injection than does a commercially used Gd III agent and also produces similar T1 relaxivity in serum phantoms at 4.7 T and 37 °C. Comparison of four different Fe III macrocyclic complexes elucidates the factors that contribute to relaxivity in vivo including solution speciation. Variable‐temperature 17 O NMR studies suggest that none of the complexes has a single, integral inner‐sphere water that exchanges rapidly on the NMR timescale. MRI studies in mice show large in vivo differences of three of the Fe III complexes that correspond, in part, to their r1 relaxivity in phantoms. Changes in overall charge of the complex modulate contrast enhancement, especially of the kidneys. Abstract : High‐Spin‐Eisen(III)‐Komplexe mit einer freien Koordinationsstelle, die Lösungsmittelwechselwirkungen ermöglicht, sind effektive T 1 ‐MRT‐Kontrastmittel in Phantomen und lebenden Mäusen. Ein koordinierter Wasserligand und die Deprotonierung einer Alkoholfunktion stabilisieren das dreiwertige Eisenzentrum, um starke Wechselwirkungen mit Wasser in der zweiten Koordinationssphäre zu erzeugen.